(untitled) (diségno, 2024)
Within the rich and heterogeneous panorama of activities that the Unione Italiana per il Disegno, in line with the principles of its statute, organizes in favour of its members and more generally for the scientific drawing community, the Training [1] and Scientific Production and Evaluation [2] commissions worked together to plan and implement a seminar dedicated to the topic of scientific evaluation. The event held in Rome on 14 March 2024 with the title Seminario informativo, formativo, sulla valutazione continues a tradition –previously established in the years 2019, 2020 and 2022 [3]– of inviting the scientific community of the area of Drawing to a critical reflection on the best practices of evaluation and self-evaluation of research and the consequent implications in the training field, considering them within current and future scenarios. [read more]